Pollution Control in Oil, Gas and Chemical Plants - Bahadori, Alireza; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This unique book covers the fundamental requirements for air, soil, noise and water pollution control in oil and gas refineries, chemical plants, oil terminals, petrochemical plants, and related facilities. Coverage includes design and operational considerations relevant to critical systems such as monitoring of water pollution control, equipment, and engineering techniques as well as engineering/technological methods related to soil, noise and air pollution control. This book also: ·         Covers a diverse list of pollution control strategies important to practitioners, ranging from waste water gathering systems and oil/suspended solids removal to chemical flocculation units, biological treatment, and sludge handling and treatment ·         Provides numerous step-by-step tutorials that orient both entry level and veteran engineers to the essentials of pollution control methods in petroleum and chemical industries ·         Includes a comprehensive glossary providing readers with an excellent guide to the variety of terminologies applicable to pollution control technologies ·         Presents the most up-to-date understanding of pollution control problems based on industry best practices and current research data Pollution Control in Oil, Gas and Chemical Plants is an ideal book for engineers and technical managers in a range of industries. Praise from a Reviewer: “To my knowledge, the present book is unique in terms of technical and engineering points in pollution control, which is as a core element in the oil and gas industry. Particularly, process engineering, design tips, and predictive tools are not found elsewhere.  In my opinion, the book is very interesting and helpful for researchers focusing on the areas of pollutants identification and pollution control and development of new technology to minimize the various kinds of pollution potentials in oil, gas and chemical industrial plants.” —Sohrab Zendeboodi, University of Waterloo, Waterloo, Ontario, Canada.
Air Pollution Control -- Water Pollution Control.- Soil Pollution Control -- Noise Pollution Control.
Keywords: Engineering design; Water pollution; Waste management; Fossil fuels; Chemical engineering; Water quality; Engineering Design; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Waste Management/Waste Technology; Fossil Fuels (incl. Carbon Capture).; Industrial Chemistry/Chemical Engineering; Water Quality/Water Pollution